A 3-D printed vitrification device integrated with French straws. (October 2022) - Tiersch, Nolan J.; Paulsen, Jacqueline; Liu, Yue; Tiersch, Terrence R.
Graphical abstract: Abstract: The goal of this work was to develop prototypes of open-hardware vitrification devices for sperm cryopreservation that can be integrated with existing straw platforms. The open-hardware Vitrification Device for French Straws (VD-FS) is low-cost, customizable, 3-D printable, standardized, and allows long-term sample storage and identification. The feasibility was shown for vitrifying and storing samples with multiple configurations. The results can be improved by design alternation and evaluation of various vitrification solutions. This is the first complete open-hardware vitrification device that can be integrated with existing French-straw storage systems, providing a foundation for future community-level modifications and improvements.